Paris 1918 : the war diary of the British ambassador, the 17th Earl of Derby - Derby, Edward George Villiers Stanley, Earl of, 1865-1948 (Liverpool historical studies, 2001)
The diary of the 17th Earl of Derby, once thought to have been lost, provides a detailed and important account of the last months of the First World War as seen through the eyes of the British Ambassador in Paris. Derby was in many ways an unlikely choice as ambassador. He was not a diplomat and could not, on his arrival, speak French. His appointment owed much to Lloyd George's determination to remove him from his previous post as Secretary of State for War. But, after a somewhat uncertain start, he proved to be a very successful ambassador upon whom successive Foreign Secretaries, Arthur Bal.